Optimization of an acetate reduction pathway for producing cellulosic ethanol by engineered yeast. Issue 12 (21st September 2016) - Zhang, Guo‐Chang; Kong, In Iok; Wei, Na; Peng, Dairong; Turner, Timothy L.; Sung, Bong Hyun; Sohn, Jung‐Hoon; Jin, Yong‐Su
ABSTRACT: Xylose fermentation by engineered Saccharomyces cerevisiae expressing NADPH‐linked xylose reductase (XR) and NAD + ‐linked xylitol dehydrogenase (XDH) suffers from redox imbalance due to cofactor difference between XR and XDH, especially under anaerobic conditions. We have demonstrated that coupling of an NADH‐dependent acetate reduction pathway with surplus NADH producing xylose metabolism enabled not only efficient xylose fermentation, but also in situ detoxification of acetate in cellulosic hydrolysate through simultaneous co‐utilization of xylose and acetate. In this study, we report the highest ethanol yield from xylose (0.463 g ethanol/g xylose) by engineered yeast with XR and XDH through optimization of the acetate reduction pathway. Specifically, we constructed engineered yeast strains exhibiting various levels of the acetylating acetaldehyde dehydrogenase (AADH) and acetyl‐CoA synthetase (ACS) activities. Engineered strains exhibiting higher activities of AADH and ACS consumed more acetate and produced more ethanol from a mixture of 20 g/L of glucose, 80 g/L of xylose, and 8 g/L of acetate. In addition, we performed environmental and genetic perturbations to further improve the acetate consumption. Glucose‐pulse feeding to continuously provide ATPs under anaerobic conditions did not affect acetate consumption. Promoter truncation of GPD1 and gene deletion of GPD2 coding for glycerol‐3‐phosphate dehydrogenase to produce surplus NADH also did not lead to improved acetate consumption. When a cellulosic hydrolysate was used, the optimized yeast strain (SR8A6S3) produced 18.4% more ethanol and 41.3% less glycerol and xylitol with consumption of 4.1 g/L of acetate than a control strain without the acetate reduction pathway. These results suggest that the major limiting factor for enhanced acetate reduction during the xylose fermentation might be the low activities of AADH and ACS, and that the redox imbalance problem of XR/XDH pathway can be exploited for in situ detoxification of acetic acid in cellulosic hydrolysate and increasing ethanol productivity and yield. Biotechnol. Bioeng. 2016;113: 2587–2596. © 2016 Wiley Periodicals, Inc. Abstract : Acetate, a major fermentation inhibitor present in lignocellulosic hydrolysate, can be co‐consumed with xylose synergistically to produce ethanol via an acetate reduction pathway, allowing both efficient xylose fermentation and in situ detoxification of acetate in lignocellulosic hydrolysate. Enzymatic activities of ACS and AADH were identified as limiting factors of the acetate reduction pathway, and optimization of the expression levels of ACS and AADH led to enhanced co‐fermentation of xylose and acetate.